BRASS COATING DEFECTS AND THEIR IMPACT ON THE QUALITY OF THIN BRASS WIRE - I. V. Borisovets; V. I. Voznaya; A. A. Saharnaya (Литьë и металлургия, 2013)
Influence of the defects of brass covering on quality of the thin brass-covered wire produced in conditions of steel-wire shops of Belorussian metallurgical plant is shown.